Can antibiotics for enteritis or for urinary tract infection disrupt the urinary microbiota in rats? - Liu, Fengping; Hu, Lei; Sheng, Jiayi; Sun, Yifan; Xia, Qiang; Tang, Yifan; Jiang, Peng; Wei, Shichao; Hu, Jialin; Lin, Hao; Xu, Zhenyi; Guo, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: To establish antibiotic pre-treatment regimes and administration routes for studies on urinary microbiota. Methods and materials: Antibiotics for enteritis (Abx-enteritis) and UTIs (Abx-UTI) were administered via gavage and/or urinary catheterisation (UC) for 1 and/or 2 weeks. The effects of these Abx on the urinary microbiota of rats were examined via 16S rRNA sequencing and urine culture. Additionally, the safety of the Abx was examined. Results: Abx-enteritis/Abx-UTI (0.5 g/L and 1 g/L) administered via gavage did not alter the microbial community and bacterial diversity in the urine of rats (FDR > 0.05); however, Abx-UTI (1 g/L) administered via UC for 1 and 2 weeks altered the urinary microbial community (FDR < 0.05). Rats administered Abx-UTI (1 g/L) via UC for 1 week demonstrated a distinct urinary microbiota in culture. Abx-enteritis/Abx-UTI administered via gavage disrupted the microbial community and reduced bacterial diversity in the faeces of rats (FDR < 0.05), and Abx-UTI administered via UC for 2 weeks (FDR < 0.05) altered the fecal microbiota. Abx-UTI (1 g/L) administered via UC did not alter safety considerations. Conclusions: Administration of Abx-UTI via UC for 1 week can be considered a pre-treatment option while investigating the urinary microbiota.